Arquitetura-suporte para a moradia popular - Bianca Feijão de Meneses (2023)
Historically, the need for having a place to live, considering the Brazilian context of unmet rights, motivates the provision of housing by its residents (voluntarily or involuntarily), who become centrally involved in a simultaneously inventive and susceptible to violence process. Such practice is the subject of study in this master’s dissertation: self-built popular housing, whose interpretation is primarily based on – and beyond layers of stigmas – the resident’s autonomous guidance in the decision-making process concerning their housing. From this point of view is possible to draw a parallel with reflections from the 1960s, specifically, John Habraken’s support theory, based on the rescue of the relationship established between resident and dwelling. This relationship becomes possible through a collaborative process, based on reconciling decisionmaking by different agents, which today finds a place in the theoretical-methodological-propositional approach of Open Building. In this regard, a relevant intersection is visualized between the theory and practice presented, which is evident in the resident’s decision-making process and leads to the following research question: how can the intersection between self-built popular housing and Open Building create bases for a shared process of design, construction, and use in contemporary housing production? To answer this, a survey of strategies was developed, based on the concept of Pierre Bourdieu’s practice and from the perspective of self-construction, Open Building, and Brazilian architectural practices, which resulted in the construction of a systematized framework of strategies. This exercise subsequently enabled the proposition of a supportive architecture for popular housing: a set of design strategies for a shared housing production process, based on repositioning the architect and urban planner, proposing a habitable, secure, and flexible support from which residents can decide according to their needs, preferences, and inclinations. Lastly, a technical document was prepared initially intended to contribute to architectural practices and its collaborators, compiling all the strategies developed for possible incorporation into architectural projects for popular housing. This is, therefore, a research that starts from a theoretical reflection and then achieves a propositional contribution to the field of architectural design, aimed at architects and architecture students, with a view to assisting in the development of more flexible and safe housing projects for its residents.